Exploring an Overview of Applied Theater in Education - Cao, Wenqi (Transactions on Social Science, Education and Humanities Research, 2024)
With the deepening of education reform, the traditional concept of education cannot adapt to the development of the times, the development of Internet technology, but also people's mode of thinking to produce far-reaching impact: the audience is not just a spectator, but a co-performer of the show. The audience should not just passively accept the transmission of information but need to be actively integrated, with common sense. The integration of applied theater and the art of teaching is a new way of teaching that has a history and is in line with the trends of the times. To give full play to the unique value of the theater, the stage, and the audience as one, to convey the power of truth, goodness, and beauty, to play a positive role in education, to bring students a new educational experience and teaching insights, through the participation of the students to improve the students and the actual life of the divergent thinking, to better improve the overall quality of the students. This study found that combining applied drama and multidisciplinary education can play a greater value. Applied drama can not only promote the participants' cognitive behavioral changes, but also the viewers can actively participate in their way, obtaining inspiration and life lessons, the diversity of drama forms enriches the emotional experience of the viewers, so that the blueprints depicted by the people for a better life and the real portrayal.